Towards A Theory Of Cross-Media Networked Microcelebrity: Of Bedrooms, Blogsites, Broadcasts, And Boardrooms - Lundmark, Evelina (AoIR Selected Papers of Internet Research, 2017)
The purpose of my research is to examine the new visibility of atheism and non-religion in a sphere that blurs private and public. In this paper I will look at how US women performing and constructing atheist identity via personal YouTube channels are enacting and invoking a counter public(s). These technologically mediated counter publics actualize issues of race, gender, religion, nationality and the issue of having voice in broader US society. These women speak of vulnerability, stereotyping, and the wish both to be seen and to remain hidden. My study highlights issues of what it means to have privacy in a hyper mediated sphere, and how intimacy is invoked in network spaces to connote authenticity. Using Actor Network Theory (ANT) I will be looking at these performances as relational and embedded in a particular nexus of technology, associative logic, templates of behavior, as well as material affordances and objects (Latour 2005). The purpose is to look at lived non-religion, not in order to categorize or make sense of the non-religious but to look at the performance of the personal and stigmatized in an ambivalent public. As a complement to ANT I appropriate Lynn Schofield Clark’s (2011) usage of mediatization theory, her usage is dynamic and emphasizes agency, if not necessarily intent, and contributes to a discussion on rethinking the conceptualization of public sphere and public discourse. I will use ANT to develop mediatization theory, particularly exploring if and how mediatization can be understood on a micro level.